2010
DOI: 10.4161/isl.2.2.11171
|View full text |Cite
|
Sign up to set email alerts
|

Electrical activity in pancreatic islet cells: The VRAC hypothesis

Abstract: A major aspect of stimulation of β-cell function by glucose is the induction of electrical activity. The ionic events that underlie β-cell electrical activity are understood in some detail. At sub-stimulatory glucose concentrations, the β-cell is electrically 'silent'. Increasing the glucose concentration to stimulatory levels results in a gradual depolarisation of the membrane potential to a threshold potential where 'spikes' or action potentials are generated. These action potentials represent the gating of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 96 publications
(99 reference statements)
3
63
0
Order By: Relevance
“…Glucose still induces electrical activity and insulin secretion even when K ATP channels are inactivated (24,25,35,36). Chloride levels in β cells are known to be important for insulin secretion, and chloride channel(s) have been proposed as part of the background channels contributing to the regulation of electrical activity and insulin secretion in β cells, although the identity of such a channel remains elusive (24,25). It has been reported that ANO1 knockdown reduces chloride ion transport in diverse cell types (37), although islets have not been studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Glucose still induces electrical activity and insulin secretion even when K ATP channels are inactivated (24,25,35,36). Chloride levels in β cells are known to be important for insulin secretion, and chloride channel(s) have been proposed as part of the background channels contributing to the regulation of electrical activity and insulin secretion in β cells, although the identity of such a channel remains elusive (24,25). It has been reported that ANO1 knockdown reduces chloride ion transport in diverse cell types (37), although islets have not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose increases chloride efflux in β cells, which could contribute to membrane depolarization (20)(21)(22)(23). Although the identity of the chloride channel(s) in β cells remains unclear, it has been proposed that certain unidentified chloride channels expressed in the plasma membrane might be involved in the regulation of electrical activity and insulin secretion in β cells (24,25). Because glucose quickly increases ANO1 gene expression, we investigated whether ANO1, the membrane calciumactivated chloride channel gene known to be expressed at a significant level in human islets (Fig.…”
Section: Ins-ano1mentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, VRAC activation results in Cl -efflux generating an inward (depolarizing) current. Glucose and several stimuli of b-cell function have been shown to activate the conductance, possibly as a result of increased b-cell volume [4,6]. VRAC activation could subsequently contribute towards electrical and secretory activity.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of FFAs consisted of an initial enhancement and subsequent suppression of glucose-induced electrical activity, and were attributed predominantly to the activation, followed by an inhibition, of the volume-regulated anion channel (VRAC). The putative role of this conductance in the pancreatic b-cell has been reviewed elsewhere [4,6]. Briefly, VRAC activation results in Cl -efflux generating an inward (depolarizing) current.…”
Section: Introductionmentioning
confidence: 99%